Quote:
Originally Posted by jasishappy

1. (sqrt(a))^3x = (a^(x^2))((a^(1/7))^(52x))
a^(3x/2) = (a^(x^2))(a^((5/7)(2x/7)))
a^(3x/2) = a^(x^2 (2/7)x (5/7))
(3/2)x = x^2 (2/7)x (5/7)
0 = x^2 (25/14)x (5/7)
Use quadratic formula to find x = 2.12 or 0.34
2. 2^(1) = log9(logx(1/343))
(1/2) = log9(logx(1/343))
9^(1/2) = logx(1/343)
3 = logx(1/343)
x^3 = (1/343)
x = (1/7)
Note: The sqrt(9) = +3 and 3, but we cannot use 3 because it gives us x = 7 and if we plug it back into the original equation then we get log9(3) which is not defined.
3. I'm not sure about this one.